Inovações curriculares e metodológicas no curso de graduação em enfermagem: impasses e contradições - Cavalcante, Marcela Maria Faria Peres (2011)
The study investigated changes in undergraduate education in nursing and the challenges and contradictions arising from the change process. We started from the consideration that today, in nursing courses, there is a strong presence of active teaching methodologies to promote in students a higher degree of activity and role in the learning process. These methodologies are very valuable to promote the activity of the student but does not have its focus centered on the concept formation and development of theoretical thinking of the student, as has the methodology proposed by V. V. Davydov, the theory of developmental teaching. With this consideration, the main question that was investigated in this study was: what contributions have the principles of the theory of Davydov in a nursing course emphasizes active methods that already? The overall objective was to conduct a teaching experiment involving insulin content, based on the principles of the theory of Davydov, to analyze their contributions to drive change in a course that already use active methods. Based on historical-cultural theory of Vygotsky and the developmental teaching theory of Davydov, the research was qualitative in nature as a procedure with the teaching experiment. We chose a nursing degree course using active methods and the subjects were students of the 5th cycle of this course and a teacher. Data collection took place through interviews, observations and analysis of school documents. The qualitative data analysis sought to capture the contradictions and dilemmas in the process of change in course from the use of active methods and repercussions of the teaching experiment with the methodology proposed by Davydov and contradictions arising. There was the presence of some contradictions and deadlocks among them including: - permanence, between teachers and students, concepts and practices attached to a traditional pedagogy in a course that is in the process of change in teaching methodologies based on active ; - little interaction and active participation of students in class. During the teaching experiment guided by principles of the theory of Davydov, there was increased participation and involvement of most students. Teaching during the teaching experiment was evaluated as a good or very good experience for most students. The results show that developmental teaching can be an innovative opportunity to advance quality of graduate programs in nursing. It was concluded that the most promising aspect of using the principles proposed by Davydov was the qualitative expansion of the thinking of students, enabling its critical development, active and strong theoretical and scientific value, contributing to compose a professional profile more focused on contemporary requirements work in nursing.